Relationships between the Foot Posture Index and foot kinematics during gait in individuals with and without patellofemoral pain syndrome - Barton, Christian J (BioMed Central, 2011)
BACKGROUND: Foot posture assessment is commonly undertaken in clinical practice for the evaluation of individuals with patellofemoral pain syndrome (PFPS), particularly when considering prescription of foot orthoses. However, the validity of static assessment to provide insight into dynamic function in individuals with PFPS is unclear. This study was designed to evaluate the extent to which a static foot posture measurement tool (the Foot Posture Index - FPI) can provide insight into kinematic variables associated with foot pronation during level walking in individuals with PFPS and asymptomatic controls. METHODS: Twenty-six individuals (5 males, 21 females) with PFPS aged 25.1 ± 4.6 years and 20 control participants (4 males, 16 females) aged 23.4 ± 2.3 years were recruited into the study. Each participant underwent clinical evaluation of the FPI and kinematic analysis of the rearfoot and forefoot during walking using a three-dimensional motion analysis system. The association of the FPI score with rearfoot eversion, forefoot dorsiflexion, and forefoot abduction kinematic variables (magnitude, timing of peak and range of motion) were evaluated using partial correlation coefficient statistics with gait velocity entered as a covariate. RESULTS: A more pronated foot type as measured by the FPI was associated with greater peak forefoot abduction (r = 0.502, p = 0.013) and earlier peak rearfoot eversion relative to the laboratory (r = -0.440, p = 0.031) in the PFPS group, and greater rearfoot eversion range of motion relative to the laboratory (r = 0.614, p = 0.009) in the control group. CONCLUSION: In both individuals with and without PFPS, there was fair to moderate association between the FPI and some parameters of dynamic foot function. Inconsistent findings between the PFPS and control groups indicate that pathology may play a role in the relationship between static foot posture and dynamic function. The fair association between pronated foot posture as indicated by the FPI and earlier peak rearfoot eversion relative to the laboratory observed exclusively in those with PFPS is consistent with the biomechanical model of PFPS development. However, prospective studies are required to determine whether this relationship is causal.